Accessibility in Digital Cinema - A Proposal for Generation and Distribution of Audio Description - Domingues, Leonardo A.; Campos, Virgínia P; Araújo, Tiago M. U. de; Souza Filho, Guido L. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Technological advances in digital cinema have allowed people to encounter experiences that awaken their imagination and expose them to other realities. Experiencing these realties can be more difficult for the blind or visually impaired, however. In our cinema rooms, visual impairments create barriers that can restrict a person’s access to critical information. Therefore, we propose a solution that attempts to eliminate these barriers by using a computational system that is able to automatically generate and distribute accessible audio tracks that describe the digital cinema experience. Using mobile devices to provide the content, visually impaired participants were given the opportunity to partake in an experiment to confirm or reject the viability of the solution presented in this article. The results of the experiment demonstrated that our computational system may be a feasible solution